Ecological Aspects of ntcA Gene Expression and Its Use as an Indicator of the Nitrogen Status of Marine Synechococcus spp - Lindell, Debbie; Post, Anton F. (Applied and environmental microbiology, 2001)
Nitrogen nutrition in cyanobacteria is regulated by NtcA, a transcriptional activator that is subject to negative control by ammonium. Using Synechococcus sp. strain WH7803 as a model organism, we show that ntcA expression was induced when cells were exposed to nitrogen stress but not when they were subjected to phosphorus or iron deprivation. Transcript levels accumulated in cells grown on a variety of inorganic and organic nitrogen sources, with the sole exception of ammonium. ntcA transcription was induced when ammonium levels dropped below 1 μM and reached maximal levels within 2 h. Furthermore, the addition of more than 1 μM ammonium led to a rapid decline in ntcA mRNA. The negative effect of ammonium was prevented by the addition of l -methionine- d , l -sulfoximine (MSX) and azaserine, inhibitors of ammonium assimilation. Thus, basal ntcA transcript levels are indicative of ammonium utilization. Conversely, the highest ntcA transcript levels were found in cells lacking a nitrogen source capable of supporting growth. Therefore, maximal ntcA expression would indicate nitrogen deprivation. This state of nitrogen deprivation was induced by a 1-h incubation with MSX. The rapid response of ntcA gene expression to the addition of ammonium and MSX was used to design a protocol for assessing relative ntcA transcript levels in field populations of cyanobacteria, from which their nitrogen status can be inferred. ntcA was basally expressed in Synechococcus at a nutrient-enriched site at the northern tip of the Gulf of Aqaba, Red Sea. Therefore, these cyanobacteria were not nitrogen stressed, and their nitrogen requirements were met by regenerated nitrogen in the form of ammonium.